Implementasi Supervisi Akademik dalam Meningkatkan Kinerja Guru di MAN 2 Pasuruan - Zainal Abidin, Moch; Abidin, Zainal; Parmujianto (Mu'allim, 2024)
Academic supervision is carried out by the Head of the Madrasah through coaching, observation and competency assessment and evaluation. The aim of this research is to understand the strategy for implementing academic supervision by the Madrasah Head as an effort to develop abilities and improve teacher performance at MAN 2 Pasuruan. This research problem aims to help teachers improve their abilities, organize and manage the process of teaching and learning activities in Madrasas. This research uses a descriptive qualitative approach with case studies. Using purposive sampling and snowball sampling techniques, the data sources were from Madrasah Principals, Deputy Madrasah Principals and teachers. Collected using free guided interviews, Focus Group Discussion (FGD), field observations and documentation. Data analysis through data collection, data presentation and drawing conclusions. Checking the validity of the data through triangulation. The results of research on academic supervision programs include 1). Planning is prepared to determine achievement indicators with a cooperative and humanist approach that is determined at the beginning of each school year. 2). The implementation strategy is to determine methods and techniques that build a report and a humanist approach, either directly or indirectly, with the help of deputy heads and teachers who have been appointed and trusted in supervision. 3). The evaluation is carried out by the Head of the Madrasah periodically by determining the schedule and time at the end of the odd and even semesters after all stages of the program have been carried out completely and comprehensively.